Effects of Biogas Slurry Drip Irrigation on Growth Performance of Brassica chinensis L. and Soil Nutrient Dynamics - DongXue Yin; Jiajun Qin; Dongdong Chen; Baozhong Wang; Wei Liu; Yingxian Wang; Weijuan Lan; Zhihao Wang; Jiachen Wang (BioResources)
The optimal amount of biogas slurry was determined to improve both the yield of Brassica chinensis L. (BL) and soil quality. An experiment was set up with six sets of drip irrigation gradients (1:3 mix of biogas and water) of 12 (BS-1), 15 (BS-2), 18 (BS-3), 21 (BS-4), 24 (BS-5), and 27 (BS-6) L. Each treatment was repeated three times and irrigated eight times. The radius of drip irrigation was 1.2 m, and the dripping speed was 2 L/h. The highest plant height, fresh weight, dry weight, soluble sugar content, and protein content of 25.2 cm, 16.7 g, 1.10 g, 0.61 g/100 g, and 1.90 mg/g, respectively, were obtained under the BS-5 treatment. Soil total nitrogen, available phosphorus, and organic matter content under the BS-4 treatment increased 5.29%, 230.75%, and 1.00%, respectively, compared with those before drip irrigation treatment. The soil available potassium content was highest under the BS-3 treatment and had increased 20.4% compared with that before drip irrigation treatment. The most remarkable influence on the yield and quality of BL was observed when the drip irrigation amount was 24 L. Drip irrigation with 21 L of biogas slurry is conducive to improving soil physical and chemical properties.